Identificação de antocianinas em raízes de Eichhornia crassipes (Mart.) Solms - Cruz, Ana Tereza de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Anthocyanins are natural products that belong to the group of flavonoids, showing color that can vary from red to blue, being used as natural dyes. These substances are known, as well, because of their antioxidant properties and that they are able to interact with metal species. Water hyacinth (Eichhornia crassipes (Mart.) Solms, Pontederiaceae) is a macrophyte used in the decontamination of aquatic environments, due to its ability to absorb metals and other pollutants. Preliminary phytochemical studies have reported the isolation and identification of anthocyanins esterified with malonic acid in the flowers of this plant. This work aimed the identification of anthocyanins and anthocyanidins in the roots of water hyacinth, so that in further studies it can be evaluated if the absorption of metals is related to a possible complexation of these with molecules of anthocyanins. The roots of the plant were extracted with methanol in acid medium. The fractions were analysed by High Performance Liquid Chromatography coupled to Diode Array Detector and Mass Spectrometry (HPLC-DAD-MS). After the analysis, it was possible to identify the presence of delphinidin-3-O-glycoside and 6-hydroxy-petunidin-3-O-glycoside, besides others...

Antocianinas são produtos naturais pertencentes ao grupo dos flavonoides, apresentando coloração que pode variar do vermelho ao azul, sendo utilizadas como corantes naturais. Essas substâncias são conhecidas também por possuírem propriedades antioxidantes e serem capazes de interagir com espécies metálicas. O aguapé (Eichhornia crassipes (Mart.) Solms, Pontederiaceae) é uma macrófita utilizada na descontaminação de ambientes aquáticos, devido à sua capacidade de absorver metais e outros poluentes. Estudos fitoquímicos prévios relatam o isolamento e identificação de antocianinas esterificadas com ácido malônico das flores dessa planta. Este trabalho visou à identificação de antocianinas e antocianidinas nas raízes do aguapé, de modo que em estudos futuros possa avaliar se a absorção de metais está relacionada com a possível complexação destes com moléculas de antocianinas. As raízes da planta foram extraídas com metanol em meio ácido. As frações obtidas foram analisadas por Cromatografia Líquida de Alta Eficiência acoplada a Detector de Arranjo de Diodos e Espectrometria de Massas (CLAE-DAD-EM). Após as análises foi possível identificar a presença de delfinidina-3-O-glicosídeo e 6-hidroxi-petunidina-3-O-glicosídeo, além de outras...
Keywords: Antocianinas; Eichhornia; Flavonoides; Cromatografia líquida de alta eficiência; Espectrometria de massa; Anthocyanins